2018
DOI: 10.21873/anticanres.12937
|View full text |Cite
|
Sign up to set email alerts
|

Detection of KK-LC-1 Protein, a Cancer/Testis Antigen, in Patients with Breast Cancer

Abstract: Background: Kita-Kyushu lung cancer antigen-1 (KK-LC-1) is a cancer/testis antigen and predominant target for cancer immunotherapy. Its detection is only established based on gene expression. In this study, we established a monoclonal antibody against KK-LC-1 to detect its protein expression in formalin-fixed samples. Materials and Methods: The monoclonal antibody against KK-LC-1 was evaluated and the detection of KK-LC-1 between gene expression and protein expression was compared in patients with breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 14 publications
3
15
0
Order By: Relevance
“…Further investigations must be performed to elucidate the potential of targeting SP17 by immunotherapy. CT83 is also expressed in multiple cancers, such as breast, gastric, and lung cancers, and the expression can be upregulated by DNMTis ( 62 67 ). CT83 as a target for TCR-based therapies has shown promising results ( 64 , 68 ), but the potential of the antigen as a target for CAR T-cell therapy remains unexplored.…”
Section: Cancer/testis Antigens As Targets For Car T-cell Therapymentioning
confidence: 99%
“…Further investigations must be performed to elucidate the potential of targeting SP17 by immunotherapy. CT83 is also expressed in multiple cancers, such as breast, gastric, and lung cancers, and the expression can be upregulated by DNMTis ( 62 67 ). CT83 as a target for TCR-based therapies has shown promising results ( 64 , 68 ), but the potential of the antigen as a target for CAR T-cell therapy remains unexplored.…”
Section: Cancer/testis Antigens As Targets For Car T-cell Therapymentioning
confidence: 99%
“…Interestingly, the aberrant expression of CT83 in the stomach is associated with Helicobacter pylori infection and atrophic status, and its expression in precancerous gastric lesions was considered as a potential predictor of gastric cancer 83 85 . Regarding CT83 in breast cancer, several studies have identified and emphasized its TNBC specificity but with a limited sample size 37 , 86 , 87 . Compared with previous findings, our data provided much stronger evidence to support this by analyzing its expression in 3617 breast cancer tissues and 71 breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…KK-LC-1/CT83/ CXorf6/MAMLD1 was found to be a critical gene in hypospadias and plays a less important role in testosterone production during the critical time for sex development [83,84]. KK-LC-1 was found in all TNBC tumours and all tumours without ER expression, with gene and protein expressions of 11.8% and 52.9%, respectively [68]. In another study, it was found that 53% of TNBC patients expressed CXorf61 in at least 30% of their tumour cells, whereas expression was strictly restricted to the testes in normal human tissues (Table 1) [67].…”
Section: Ctas With Increased Expression In Tnbc But With Unclear Implicationsmentioning
confidence: 98%